A Phloem-Expressed PECTATE LYASE-LIKE Gene Promotes Cambium and Xylem Development - Bush, Max; Sethi, Vishmita; Sablowski, Robert (Frontiers in Plant Science, 2022)
The plant vasculature plays essential roles in the transport of water and nutrients and is composed of xylem and phloem, both of which originate from undifferentiated cells found in the cambium. Development of the different vascular tissues is coordinated by hormonal and peptide signals and culminates in extensive cell wall modifications. Pectins are key cell wall components that are modified during cell growth and differentiation, and pectin fragments function as signals in defence and cell wall integrity pathways, although their role as developmental signals remains tentative. Here, we show that the pectin lyase-like gene PLL12 is required for growth of the vascular bundles in the Arabidopsis inflorescence stem. Although PLL12 was expressed primarily in the phloem, it also affected cambium and xylem growth. Surprisingly, PLL12 overexpression induced ectopic cambium and xylem differentiation in the inflorescence apex and inhibited development of the leaf vasculature. Our results raise the possibility that a cell wall-derived signal produced by PLL12 in the phloem regulates cambium and xylem development.